Rozwój sektora prywatnych ubezpieczeń zdrowotnych w Polsce w latach 2000-2003 - Szmigiel, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Widely criticized low efficiency of the public health care system in Poland, makes up an area for the development of private, voluntary health insurance sector. The purpose of this work is to define the current state of private health insurance sector as well as their place in the Polish health care system. The valuation attempt of development tendencies characteristic of commercial health insurance market is taken in the paper. To this end, the conducted analysis contains indexes that may be treated as economical measurements of the development of the private health insurance market. The main factors and prospects of the further growth of voluntary health insurance sector are presented in the paper as well. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 284-291